PERANCANGAN MESIN GERGAJI KAYU UNTUK PERAJIN PALLET KAYU - Akhmad Syarief; Aditya Eko Kristanto (Scientific Journal of Mechanical Engineering Kinematika, 2019)
Technology at all times continues to grow along with the progress of the times, not least in the furniture industry. In the development of timber techniques demands a quality product, it needs an effective and efficient process. This is also the underlying work of cutting timber. Initially the cutting of the wood was done manually by utilizing manpower and then changed using a whipsaw. The rapid development of technology makes hand saws rarely used and switches using sawing machines and saw tables. From the results of the design process of wood sawing machine summed up some things as follows: Dimensions of wood cutting machine 1500 × 1000 × 800 mm, saws used in circular or cyrcle wood cutting machine with a circular motion saw blade, The rotation is passed from the motor to the saw blade is not in the fox and using the same pulleys of 74 mm diameter, wood cutting machine using 2Hp power, the level of safety on the wood cutting machine after theoretical calculations ranging from the transmission system, axis, and frame that is 9.524 m / sec belt speed is said to be good because ≤ 30 m / sec. The axle is said to be safe because the shear stresses that occur in the shaft are smaller than the allowable shear stress of , and on the framework of the wood cutting machine the yield of the voltage is less than the yield strength material of 7,888 Mpa ≤ 207 MPa with deflection 0,096 mm, In transmission belt V used is V type A42 belt, Image modification work of wood cutting machine used for machine making process contained in attachment.